2021
DOI: 10.3389/fpsyg.2020.558287
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in the Endurance Runner: The Role of Self-Regulatory Modes and Basic Psychological Needs

Abstract: Endurance sports certainly require an important and delicate task of mental and physical reintegration from the impact of the fatigue induced by the exertion of the sport performance. The topic of the resilience of athletes has been the theme of numerous studies, however, there are few specific works on the psychological resilience of runners. Our study aimed to investigate Resilience in Endurance Runner related to the role of Self-Regulation Modes and Basic Psychological Needs. Especially, the aim of our work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 58 publications
2
18
0
2
Order By: Relevance
“…Being intrinsically motivated leads individuals to experience pleasant emotions and to feel free and relaxed [ 27 ]. Several studies have shown that intrinsic motivation is a crucial factor in learning over an individual’s entire lifespan [ 7 ] and that it has positive effects on well-being and life satisfaction, persistence, participation in activities and high levels of performance [ 5 , 19 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being intrinsically motivated leads individuals to experience pleasant emotions and to feel free and relaxed [ 27 ]. Several studies have shown that intrinsic motivation is a crucial factor in learning over an individual’s entire lifespan [ 7 ] and that it has positive effects on well-being and life satisfaction, persistence, participation in activities and high levels of performance [ 5 , 19 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SDT emphasizes the psychological needs and motivations of human behavior, particularly autonomy. Given that many runners have demonstrated the characteristics of being motivational, serious, autonomous, and resilient to their pursuit of this activity [ 36 , 37 ]. SDT could be applied to determine whether running race participants are motivated intrinsically or extrinsically.…”
Section: Discussionmentioning
confidence: 99%
“…Найбільш тривалими змаганнями щодо особливостей рухової діяльності є бігові дисципліни. У свою чергу змагання у горизонтальних стрибках передбачають тривалу участь спортсменів у змаганнях через особливості правил змагань [4,8]. При цьому легкоатлетичні багатоборства передбачають дводенну участь в інтенсивній різноманітній руховій діяльності.…”
Section: Zhoglo V Matuzna N Kazak V Fomenko V Yefremenko a Psychologi...unclassified